A comparative analysis of online news websites Rappler, Inquirer.net and Philstar.com on the coverage of Ramadan and Christmas in the year 2015 - Roque, Earl Jed Garcia
"This thesis analyzed the stories on Ramadan and Christmas in the year 2015 in news websites, Rappler, Inquirer.net, and Philstar.com to compare if the differences in the attention provided by the media in both religious events and explored the possible framing patterns to such occasions. The thesis used a content analysis of all the articles filed under Ramadan and Christmas on these news websites."